29.2k views
3 votes
What is the solution to the equation 1/2 x + 3 = 2/3 x + 1​

User Yossarian
by
4.8k points

1 Answer

4 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


(1)/(2) x + 3 = (2)/(3) x + 1 \\

Subtract sides 3


(1)/(2) x + 3 - 3 = (2)/(3) x + 1 - 3 \\


(1)/(2) x = (2)/(3) x - 2 \\

Multiply sides by 6


6 * (1)/(2) x = 6 * (2)/(3) x + 6 * ( - 2) \\


3x = 4x - 12

Subtract sides 4x


- 4x + 3x = - 4x + 4x - 12


- x = - 12

Negatives simplifies


x = 12

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

CHECK :


(1)/(2) (12) + 3 = (2)/(3) (12) + 1 \\


6 + 3 = 8 + 1


9 = 9

Thus the solution is correct .

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Remi Smirra
by
5.0k points